Test for Inhibition of the Enzyme Α-Glucosidase Fraction of Ethanol Extract of Onco Leaves (Spondias pinnata (L.f.) Kurz.) and the Antidiabetic Activity of the Selected Fraction - Pagal, Fajria Rezky Priyanti Amara; Sunarni, Titik; Supriyadi, Supriyadi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Degenerative diseases are the number one disease in Southeast Asia. Based on WHO data in 2008, the death rate in Southeast Asia was around 14.5 million, around 55% (7.9 million) caused by degenerative diseases. One of the degenerative diseases is diabetes mellitus. Diabetes mellitus is a metabolic disorder characterized by hyperglycemy. Research that has been carried out to look at the antidiabetic activity of onco (Spondias pinnata (L.f.) Kurz) leaves is still limited to the extraction results. Objectives: This study aims to determine the fraction of onco leaf ethanol extract in inhibiting the enzyme alpha glucosidase, having antidiabetic activity and histopathological picture of pancreatic cells in streptozotocin-induced male white rats (Rattus norvegicus). This study used inhibition testing of the enzyme α-glucosidase fraction of onco leaf ethanol extract with concentrations of 12.5, 25, 50,100 and 200 μg/mL using a microplate reader with a wavelength of 405 nm, as well as with experimental laboratory test animal methods as many as 28 mice divided into 7 treatment groups the induced streptozotocin except the normal group. Group I as normal control of rats that were only given regular drinking food, group II as negative control without treatment, group III as positive control using glibenclamide drugs and group IV ethanol extract 500, V n-hexane fraction 132.54, VI ethyl acetate fraction 126.24 and VII water fraction 239 mg/KgBB treatment given for 14 days. The results showed that onco leaf ethanol extract inhibits the enzyme α-glucosidase with very strong strength (IC50 = 39.13 μg / ml) and the n-hexane fraction has the effect of reducing glucose levels as well as the ability to correct the histopathology of the pancreas of male white rats (Rattus norvegicus) induced streptozotocin. Conclusions: Ethanol extract and the fraction of onco leaves (Spondias pinnata (L.f.) Kurz) has antidiabetic activity with a mechanism of action inhibiting the enzyme alpha glucosidase and the activity of decreasing blood glucose levels and has the ability to correct the histopathology of the pancreas of male white rats (Rattus norvegicus) induced streptozotocin.